2006
DOI: 10.1016/s1880-4276(06)80014-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Therapy on Heart Rate Variability in Elderly Patients with Cerebral Vascular Disease and Dementia

Abstract: Objective: In Japan, the number of elderly people with cerebral vascular disease (CVD) and dementia is increasing, resulting in increased expenditures to treat such patients. Reports indicate that music therapy can reduce anxiety in patients with myocardial infarction. However, it is unclear whether music therapy can have beneficial effects on very elderly patients with CVD and dementia, as these conditions may influence cardiac autonomic nerve functions. Therefore, we investigated the effects of music therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Apart from these discrepancies, outcomes measured in more than one study (excluding those results not yet published [76] ) tended to change in the same way. Both studies measuring salivary cortisol reported no statistically significant changes [68,69] , and all studies measuring HRV reported changes indicative of increased parasympathetic activity [67,73,74,75] .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Apart from these discrepancies, outcomes measured in more than one study (excluding those results not yet published [76] ) tended to change in the same way. Both studies measuring salivary cortisol reported no statistically significant changes [68,69] , and all studies measuring HRV reported changes indicative of increased parasympathetic activity [67,73,74,75] .…”
Section: Discussionmentioning
confidence: 95%
“…In terms of the outcomes measured, seven of the 13 papers measured a cardiovascular outcome [67,68,72,73,74,75,76] , eight of the papers measured an endocrinological outcome [63,64,65,66,67,68,69,70] , one measured galvanic skin responses but did not publish the data [76] , and one measured rate of respiration [72] . Also, four studies measured more than one kind of outcome [67,68,72,76] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations